2014
DOI: 10.4088/jcp.13m08820
|View full text |Cite
|
Sign up to set email alerts
|

Glucometabolic Hormones and Cardiovascular Risk Markers in Antipsychotic-Treated Patients

Abstract: Objective: Treatment with antipsychotic drugs is widely associated with metabolic side effects such as weight gain and disturbed glucose metabolism, but the pathophysiologic mechanisms are unclear.Method: Fifty nondiabetic (fasting plasma glucose ≤ 7.0 mmol/L), antipsychotic-treated male patients (ICD-10 diagnosis code F20, F21, F22, F25, F28, or F60; mean ± SD age = 33.0 ± 6.7 years; body mass index [BMI; kg/ m 2 ] = 26.0 ± 4.7; waist circumference = 95.9 ± 13.3 cm; glycated hemoglobin A 1c [HbA 1c ] = 5.7% ±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 44 publications
0
11
1
Order By: Relevance
“…Controlling for the variables, which we previously reported significantly different between patients and controls (tobacco smoking, daily physical activity, as well as fasting values of proinsulin, C-peptide, and glucosedependent insulinotropic polypeptide (GIP), total cholesterol, low-density lipoprotein cholesterol, triglycerides, and CRP, and postprandial values of insulin, proinsulin, Cpeptide, and GIP (Ebdrup et al, 2014)), did not alter the findings.…”
Section: Prolactincontrasting
confidence: 48%
See 1 more Smart Citation
“…Controlling for the variables, which we previously reported significantly different between patients and controls (tobacco smoking, daily physical activity, as well as fasting values of proinsulin, C-peptide, and glucosedependent insulinotropic polypeptide (GIP), total cholesterol, low-density lipoprotein cholesterol, triglycerides, and CRP, and postprandial values of insulin, proinsulin, Cpeptide, and GIP (Ebdrup et al, 2014)), did not alter the findings.…”
Section: Prolactincontrasting
confidence: 48%
“…Details of inclusion and exclusion criteria and participants were previously reported (Ebdrup et al, 2014). In short, patients had a diagnosis in the schizophrenia spectrum [ICD-10 diagnosis: F20, F21, F22, F25, F28, F60.1] and all were Caucasian outpatients treated with at least one antipsychotic.…”
Section: Participantsmentioning
confidence: 99%
“…In contrast to a GLP‐1RA study in non‐diabetic obese patients, we found unexpected significant increases in HbA1c, fasting plasma glucose and lipids after 3 months; however, parallel increases in these parameters were also observed in the placebo group. This could indicate that these metabolic parameters in antipsychotic‐treated patients may not be as responsive to weight loss as would be expected in the background population . In contrast, a study using exenatide twice‐daily and once‐weekly in patients with type 2 diabetes found a significant lowering of HbA1c, regardless of weight loss …”
Section: Discussionmentioning
confidence: 96%
“…In this regard, our own work from preclinical rodent models consistently supports pronounced, direct effects on insulin sensitivity (peripheral and hepatic) following acute dosing of specific AP agents (e.g., risperidone, olanzapine (Ola) or clozapine) (Chintoh et al 2008(Chintoh et al , 2009. From a clinical perspective, acute or 'direct' effects are supported by reports of diabetic ketoacidosis occurring shortly after initiation of AP drugs in absence of notable weight changes (Guenette et al 2013), as well as studies that suggest a risk of glucose dysregulation independently of weight gain (Newcomer et al 2002, Henderson et al 2005, Ebdrup et al 2014. These observations support the notion that acute mechanisms can lead to glucose dysregulation in the absence of weight gain, but that over time, these can contribute to notable changes in adiposity.…”
Section: Introductionmentioning
confidence: 89%